Molecular dynamics of copolyester/clay nanocomposites as investigated by viscoelastic and dielectric analysis - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Journal of Polymer Science Part B-Polymer Physics, 2008)
We have investigated the molecular dynamics of poly(ethylene glycol-co-cycloxeane-1,4-dimethanol terephthalate) (PETG) nanocomposites based on a organically modified layered silicate. Intercalated namocomposites were prepared by melt compounding technique as evidenced from the X-ray diffraction and transmission electron microscopy studies. Two relaxation processes were observed in pure PETG as well as in the nanocomposites. The low-temperature beta-process was assigned to the local motions of C=O polar groups and the alpha-process was due to the glass-rubber transition or the segmental relaxations associated with the polymer chain backbone. Presence of layered silicates accelerated alpha-relaxation dynamics in the nanocomposites accompanied by a depression in T(g) which was attributed to the reduced intermolecular cooperativity between intercalated polymers chains. Additionally, a direct comparison between the viscoelastic and dielectric studies shows excellent agreement between the accelerated alpha dynamics of the nanocomposites. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2539-2555, 2008
Keywords: clay; Dielectric relaxation; Nanocomposites; polyesters

Magnetite/CdTe magnetic-fluorescent composite nanosystem for magnetic separation and bio-imaging - Kale, Anup; Kale, Sonia; Yadav, Prasad; Gholap, Haribhau; Pasricha, Renu; Jog, Jyoti Prakash; Lefez, Benoit; Hannoyer, Beatrice; Shastry, Padma; Ogale, Satishchandra B. (Nanotechnology, 2011)
A new synthesis protocol is described to obtain a CdTe decorated magnetite bifunctional nanosystem via dodecylamine (DDA) as cross linker. High resolution transmission electron microscopy (HRTEM), energy-dispersive x-ray spectroscopy (EDAX), vibrating sample magnetometry (VSM), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS) and fluorescence microscopy are used to characterize the constitution, size, composition and physical properties of these superparamagnetic-fluorescent nanoparticles. These CdTe decorated magnetite nanoparticles were then functionalized with anti-epidermal growth factor receptor (EGFR) antibody to specifically target cells expressing this receptor. The EGFR is a transmembrane glycoprotein and is expressed on tumor cells from different tissue origins including human leukemic cell line Molt-4 cells. The magnetite-CdTe composite nanosystem is shown to perform excellently for specific selection, magnetic separation and fluorescent detection of EGFR positive Molt-4 cells from a mixed population. Flow cytometry and confocal laser scanning microscopy results show that this composite nanosystem has great potential in antibody functionalized magnetic separation and imaging of cells using cell surface receptor antibody.

MOF derived porous carbon-Fe3O4 nanocomposite as a high performance, recyclable environmental superadsorbent - Banerjee, Abhik; Gokhale, Rohan; Bhatnagar, Sumit; Jog, Jyoti Prakash; Bhardwaj, Monika; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Materials Chemistry, 2012)
A high surface area carbon composite with Fe3O4 nanoparticles is synthesized by pyrolysis of an iron containing Metal Organic Framework (MOF). The composite can be prepared by annealing the MOF at different temperatures (500 degrees C and 600 degrees C), each case exhibiting unique properties in terms of the hydrophobic behaviour and surface area, resulting in specific applicability domains. We highlight the exceptional behaviour of this material as a magnetically separable and recyclable superadsorbent for removal and recovery of environmental pollutants (oil/hydrocarbon and dye/phenol).